APLIKASI PAKLOBUTRAZOL UNTUK MENINGKATKAN PRODUKSI TANAMAN CENGKEH MUDA (Syzygium aromaticum L.) - Paulus, Jeanne M.; Runtunuwu, Semuel D.; Moningka, Frieda F. (EUGENIA, 2020)
Clove (Syzigium aromaticum L.) is one of the important commodity crop farming, especially as a basic material in the kretek cigarette industry, also belong to the volatile oil-producing spice crops used as basic materials for pharmaceutical and food industries. The study aims were: 1) manipulating the canopy shape of clove plants to be shorter than normal, (2) obtaining the right dose to increase the productivity of young clove plants. Benefit study is to provide information technology for the farmers to increase crop productivity clove.  Research was done in the  Popareng Village,  District of Tatapaan, South Minahasa Regency in November 2011 to May 2012. Research compiled in Randomized Block Design (RBD) with one factor of treatment, consisting of four dosage of paclobutrazol (P), namely: P0 = 0 g tree-1; P1 = 1.0 g tree-1; P2 = 1.5 g tree-1 : P3 = 2.0 g  tree-1. The results showed that paclobutrazol inhibited the high growth of the apical buds is 72% at a dosage of 1.0 g tree-1, 73% at a dosage of 1.5 g tree-1 and 81% at a dosage of 2.0 g tree-1 that produces clove crop 3-year-old to be shorter than normal growth. Paclobutrazol applications increase weight 1000 grain dried flowers tree-1 and production tree-1. Highest production achieved in the paclobutrazol dosage 2.0 g tree-1, which is  0.024 kg of 1000 grain weight of dried flowers and production  tree-1 is 3.350 kg, while the lowest production in a dosage of 0.0 g paclobutrazol (control), is 0.192 kg of 1000 grain weight dried flowers and production tree-1  is 1.012 kg.